Astma : zwiezly poradnik - American Medical Association (Warszawa : Ksiazka i Wiedza, 2001)
Polish translation of "Essential guide to asthma". A guide to overcoming asthma through diet and life style.
Includes index.
Translation of: Essential guide to asthma.
Keywords: Asthma -- Popular works